Explosives series properties of explosives of military interest (U.S. Army Materiel Command, 1971)
The report is one of a series on Explosives. One hundred and ten explosive compounds or mixtures are listed alphabetically, with their properties, including composition variations. These explosives were selected because of their current or probable application to military use.
Keywords: Explosives, Military -- Handbooks, manuals, etc.; elektronické knihy; electronic books